INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK KPPI KABUPATEN PURBALINGGA - Suliyanto, Suliyanto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2008)
The aim of this research is to measure KPPI in Purbalingga Regency performance increase. Primary data was collected using proportional random sampling. Sample of this research consist of 325 respondents. The result of this research shown that KPPI in Purbalingga Regency was perform well to their society with gave satisfying service.